2007
DOI: 10.2174/138920007782798225
|View full text |Cite
|
Sign up to set email alerts
|

Xenobiotic Metabolism in Human Skin and 3D Human Skin Reconstructs: A Review

Abstract: In this review, we discuss and compare studies of xenobiotic metabolism in both human skin and 3D human skin reconstructs. In comparison to the liver, the skin is a less studied organ in terms of characterising metabolic capability. While the skin forms the major protective barrier to environmental chemical exposure, it is also a potential target organ for adverse health effects. Occupational, accidental or intended-use exposure to toxic chemicals could result in acute or delayed injury to the skin (e.g. infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 73 publications
1
35
0
Order By: Relevance
“…Nohynek et al [40] used a commercially available reconstructed human epidermis for the safety assessment of the oxidative arylamine hair dye ingredients para-aminophenol and para-phenylenediamine. Recently, by comparing xenobiotic metabolism studies both in human skin and 3D human skin reconstructs, Gibbs et al [41] suggested that skin reconstructs could became a fully defined in vitro model for investigating enzymemediated xenobiotic metabolism in the skin, and a potential alternative to animal models. However, a key issue, especially for transformed keratinocyte cell lines and 3D cell cultures, is if enzymatic patterns can be fully expressed as in vivo original cells.…”
Section: B) Skin Cell Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nohynek et al [40] used a commercially available reconstructed human epidermis for the safety assessment of the oxidative arylamine hair dye ingredients para-aminophenol and para-phenylenediamine. Recently, by comparing xenobiotic metabolism studies both in human skin and 3D human skin reconstructs, Gibbs et al [41] suggested that skin reconstructs could became a fully defined in vitro model for investigating enzymemediated xenobiotic metabolism in the skin, and a potential alternative to animal models. However, a key issue, especially for transformed keratinocyte cell lines and 3D cell cultures, is if enzymatic patterns can be fully expressed as in vivo original cells.…”
Section: B) Skin Cell Culturesmentioning
confidence: 99%
“…For example, bovine serum albumin (BSA), commonly used in receptor media in permeation studies to increase solubility of lipophilic substances, was found strongly inhibiting the metabolism of topically applied prednicarbate in reconstructed epidermis [48]. Moreover, the 6-well plate system was introduced for maintaining skin viability under optimal conditions during culture in a humidified incubator [41,49].…”
Section: In Vitro Absorption/metabolism Studiesmentioning
confidence: 99%
“…Ideally an experimental method for identifying potentially sensitising pro-electrophiles would include appropriate metabolic and abiotic activating capability reflective of that in skin. However, so little is known about skin metabolism to date (recently reviewed in Gibbs et al, 2007), that finding a suitable metabolising system could present a significant challenge in assay development.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on lipophilicity and molecular weight, the rate and route of transport across stratum corneum varies, predominating through either the lipid bilayers, corneocytes or via appendages such as sweat ducts and hair follicles (Potts and Guy, 1992;Mitragotri, 2003;Magnusson et al, 2004). Once present in the viable skin, the ingredient will distribute between extra-and intra-cellular space, where there is the potential for both phase I (activation of pro-haptens) and phase II (predominantly clearing) metabolism (Gibbs et al, 2007;Hagvall et al, 2008;van Eijl et al, 2012). Finally, the ingredient is cleared from the viable skin via the dermal capillary bed.…”
Section: Introductionmentioning
confidence: 99%